Differences in the Assessment of Safe and Risky Driving Behaviors: Pedestrians Versus Drivers. (June 2022) - Alonso, Francisco; Esteban, Cristina; Faus, Mireia; Useche, Sergio A.
Interactions between pedestrians and drivers are an important traffic safety issue. Psycho-social factors such as thoughts, perceptions and attitudes toward other people can be reliable predictors of riskier or safer behaviors among road users. The aim of this study was to assess how frequently participants perceive that drivers perform safe and risky road behaviors through drivers' self-reported behavior and pedestrians and other drivers' external perceptions. The results show that pedestrians assess the road behaviors of drivers in a seriously negative way. Meanwhile, drivers perceive their own behaviors as more appropriate than those performed by the rest of drivers. Women attribute more favorable assessments to other users' road behavior. Similarly, older drivers do the same, and consider themselves "safer" users. On the contrary, younger drivers report a higher frequency of self-rated unsafe behaviors. The study highlights the importance of working on the awareness of self-rated road behaviors. Road safety interventions and programs in Spain must consider the differences related to gender and age.